Electro-acupuncture Combined with Medical Treatment for Successful Management of Legs Paralysis in a Dog - Steven TauficLeo; LitaRakhma Yustinasari; Juliano Mwenda Ntoruru (Indian Journal of Forensic Medicine & Toxicology, 2021)
A 5-year-old Siberian Husky female dog was referred with concerned maggots and legs paralysis.The dogwas examined clinically and radiographically. Shewas positive of E. canisand Anaplasma. Major clinical signshowed thedog unable to lift the body. Neurological exam was performed, deep pain on all limbs were delayed.The dog got wound treatment and electro-acupuncturethrough perpendicular insertion into acupuncturepoints: BL-23, BL-26, BL-40, BL-60, ST-36, and LIV-3for 20 minutes/day, 70 Hz and 5A,continuously,for 15 daysand then reduce to 3 times/week.Significant improvements were observed,finally the dog beingrecovered.Thiscase showed favorable therapeutic response by alternative treatment.